Beretning om Landbrugsforsøg ved den kgl. Veterinair- og Landbohøiskole i Aaret 1861. - Jørgensen, B. S. (Tidsskrift for Landøkonomi, 2018)
Beretning om Landbrugsforsøg ved den kgl. Veterinair- og Landbohøiskole i Aaret 1861.